Respiratory Complex I dysfunction in cancer: from a maze of cellular adaptive responses to potential therapeutic strategies. (18th October 2021) - Sollazzo, Manuela; De Luise, Monica; Lemma, Silvia; Bressi, Licia; Iorio, Maria; Miglietta, Stefano; Milioni, Sara; Kurelac, Ivana; Iommarini, Luisa; Gasparre, Giuseppe; Porcelli, Anna Maria
Abstract : Mitochondria act as key organelles in cellular bioenergetics and biosynthetic processes producing signals that regulate different molecular networks for proliferation and cell death. This ability is also preserved in pathologic contexts such as tumorigenesis, during which bioenergetic changes and metabolic reprogramming confer flexibility favoring cancer cell survival in a hostile microenvironment. Although different studies epitomize mitochondrial dysfunction as a protumorigenic hit, genetic ablation or pharmacological inhibition of respiratory complex I causing a severe impairment is associated with a low‐proliferative phenotype. In this scenario, it must be considered that despite the initial delay in growth, cancer cells may become able to resume proliferation exploiting molecular mechanisms to overcome growth arrest. Here, we highlight the current knowledge on molecular responses activated by complex I‐defective cancer cells to bypass physiological control systems and to re‐adapt their fitness during microenvironment changes. Such adaptive mechanisms could reveal possible novel molecular players in synthetic lethality with complex I impairment, thus providing new synergistic strategies for mitochondrial‐based anticancer therapy. Abstract : Severe complex I (CI) dysfunction or its pharmacological inhibition have been shown to induce a quiescent phenotype in cancer cells. Despite this initial low‐proliferative status of tumor masses, these cancer cells may resume proliferation, activating adaptive molecular responses to overcome growth arrest. Such adaptive mechanisms could reveal possible novel molecular players in synthetic lethality with CI impairment, providing new findings for mitochondrial‐based anticancer therapeutic strategies.